Tradisi Penafsiran Pesantren Jawa Terhadap QS. Al-Anbiya’ [21]: 112: Kajian Komparatif Tafsir Al-Ibriz - Zar’in, Umi; Fansuri, Fuad (Indo-MathEdu Intellectuals Journal, 2026)
This study focuses on the use of language, script, presentation format, and the contextuality of interpretation that reflects the intellectual tradition of Javanese pesantren. The research aims to analyze the tradition of Javanese pesantren interpretation of QS. Al-Anbiyā’ [21]: 112 in Tafsir Al-Ibrīz. The study uses library research methods with a qualitative-descriptive approach. Primary data was obtained from Tafsir Al-Ibriz by K.H. Bisri Mustofa, while secondary data came from books, journals, and research related to Nusantara interpretation and the Javanese pesantren tafsir tradition. Data analysis was conducted qualitatively with stages of data reduction, data presentation, and conclusion drawing. The research results indicate that Tafsir Al-Ibriz has distinct characteristics of Javanese pesantrens through the use of the Javanese language and Pegon script as a medium for interpreting the Qur’an. The simple and communicative presentation format of the tafsir reflects the pedagogical style of pesantrens, aimed at facilitating the community’s understanding of the Qur’an’s contents. The interpretation of QS. Al-Anbiya’ [21]: 112 also shows a close relationship between the Qur’anic text and the socio-cultural context of Javanese society, particularly in emphasizing the values of trust in God (tawakal), patience, and social harmony. This study confirms that Tafsir Al-Ibriz is a representation of the Javanese pesantren tafsir tradition, showcasing the vernacularization process of the Qur’an within the Nusantara tafsir heritage.